TOURISM OBJECT MANAGEMENT IN WAJO REGENCY - Sampetamma, Yurike; Guntur, Muhammad; Nur, Andi Cudai (Universitas Negeri Makassar, 2025)
This study aims to determine the management of tourism objects in Wajo Regency. The type of research used is descriptive qualitative, while the data sources used in this study are primary data sources and secondary data sources with a total of 7 informants. Data collection techniques using observation, interviews, and documentation. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. The validation of the data used is source triangulation and technique triangulation. The researcher uses George R Terry's theory of management elements, which is used to assess tourism object management at the Wajo Regency Youth Sports and Tourism Office. Based on the results of the study, the management of tourism objects in Wajo Regency with reference to George R Terry's theory of management elements has not been carried out optimally. The human and financial elements are one of the inhibiting factors that the management of tourist objects has not been maximized. Likewise human resource management has not been maximized in terms of quality and quantity possessed, because the average existing human resources based on their educational background on human resources are not in accordance with the education and skills of the field of work where they are placed. In terms of quantity, the number of human resources has not been sufficient. This can be seen from the number of tourist destinations visited, which are still short of employees. Financial management cannot be said to be good because the available funds or budget are very limited and cannot meet needs, also very dependent on the regional budget so that they cannot support all tourism object management activities.